Why did Indonesia Fail to Build its First Nuclear Power Plant in Muria, Jepara? - Nugraha, Aryanta (Jurnal Paradigma, 2023)
In order to achieve net zero emission and national energy resilience BAPETEN has announced that the Indonesian government plans to build a new nuclear power plant by 2039. While the new plans to build a new nuclear power plant by 2039 remains to be seen, this article aims at revisiting the question of why did Indonesia, under President Yudhoyono administration fail to build its first nuclear power plant in Muria, Jepara. This article argues the failure to build the first nuclear power plant was caused by strong resistance to the nuclear power plant from the civil society movements due to the lack of trust towards the government in handling the risks of nuclear. Hence, any plans to build nuclear power plant in Indonesia in the future should address attentions to public trust regarding the risks of the using of nuclear energy.